PENERAPAN PUTUSAN SELA DI PENGADILAN HUBUNGAN INDUSTRIAL DALAM PERKARA PEMUTUSAN HUBUNGAN KERJA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 11 TAHUN 2020 - Chamdani Chamdani; Budi Endarto; Sekaring Ayumeida Kusnadi; Nobella Indradjaja (Universitas Muhammadiyah Ponorogo, 2022)
Almost all of the employers who terminate the employment relationship of their workers terminate their rights and obligations as employers to the workers concerned because they are no longer responsible or have ended their employment relationship with the work so that their rights and obligations are also cut off, including the decision on termination of employment determined by the entrepreneur. The purpose of this study is to analyze and determine the form of obligations of workers and employers that must be carried out during disputes over the termination of employment and to analyze the application of decisions between cases of termination of work after the enactment of Law no. 11 of 2020 concerning Job Creation. This research is a normative legal research or document or literature study carried out or aimed only at Article 96 of Law No. 2 of 2004 concerning Industrial Relations Disputes and Chapter IV Manpower Article 81 of Law No. 11 of 2020 concerning Job Creation. The interlocutory decision, as referred to in Article 96 paragraph (1) of Law No. 2 of 2004 concerning Settlement of Industrial Relations Disputes, is an interlocutory decision with the type of Interlocutor decision. Still, in its application, it is often referred to as a provisional decision and the wages granted in the interlocutory decision are called the regulated suspension wages. In the provisions of article 81, number 46 of Law no. 11 of 2020 concerning Job Creation, namely Article 157A paragraph (2) of Law no. 13 of 2003 concerning Manpower.